DNA‐binding determinants and cellular thresholds for human telomerase repeat addition processivity - Wu, Robert Alexander (EMBO J, 2017)
The reverse transcriptase telomerase adds telomeric repeats to chromosome ends. Purified human telomerase catalyzes processive repeat synthesis, which could restore the full ~100 nucleotides of (T(2) AG (3))(n) lost from replicated chromosome ends as a single elongation event. Processivity inhibition is proposed to be a basis of human disease, but the impacts of different levels of processivity on telomere maintenance have not been examined. Here, we delineate side chains in the telomerase active‐site cavity important for repeat addition processivity, determine how they contribute to duplex and single‐stranded DNA handling, and test the cellular consequences of partial or complete loss of repeat addition processivity for telomere maintenance. Biochemical findings oblige a new model for DNA and RNA handling dynamics in processive repeat synthesis. Biological analyses implicate repeat addition processivity as essential for telomerase function. However, telomeres can be maintained by telomerases with lower than wild‐type processivity. Furthermore, telomerases with low processivity dramatically elongate telomeres when overexpressed. These studies reveal distinct consequences of changes in telomerase repeat addition processivity and expression level on telomere elongation and length maintenance.